BRANDING 'SHINING BATU' AS A TOURISM PROMOTION STRATEGY IN INSTAGRAM CONTENT @DISPARTABATU - Resmawa, Ira Ningrum; Wailmi, Khil; Setiawan, Zunan; Rajab, Muhammad; Muthmainnah, Muthmainnah (ITB AAS Indonesia Surakarta, 2024)
This research aims to (1) determine the 'shining Batu' branding strategy in instagram content @dispartabatu; and (2) knowing the dimensions of tourism promotion in Instagram content @dispartabatu. This research is qualitative-descriptive research. This research describes the branding 'shining Batu' as tourism promotion in Instagram content @dispartabatu. The data analysis technique in this research consists of data presentation, data reduction, and drawing conclusions. The results of this research show that (1) the 'shining Batu' branding strategy in instagram content @dispartabatu includes brand positioning showing the geographical location of Batu as a tourism potential that other regions do not have, brand personality showing the government's ideas regarding the characteristics of the city of Batu by referring to potential, and brand identity shows the help of the culinary sector in branding Batu as a tourist city; and (2) the tourism promotion dimension in instagram content @dispartabatu contains an entertainment dimension by displaying Sanduk art as Batu's cultural identity, an interaction dimension by inviting the public to visit various interesting tourist destinations in the city of Batu, a trend dimension by uploading trends in international paragliding championships as branding for Shining Batu through sport tourism events, and customization by displaying Batu's typical Rampak Barong art.